Functional outcomes of spasticity-reducing surgery and rehabilitation at 1-year follow-up in 30 patients. (October 2020) - Bergfeldt, Ulla; Strömberg, Joakim; Ramström, Therese; Kulbacka-Ortiz, Katarzyna; Reinholdt, Carina
The effects of spasticity-reducing surgery in the upper extremity were assessed in a prospective observational study of 30 consecutive patients with stroke ( n  = 13), incomplete spinal cord injury ( n  = 9), traumatic brain injury ( n  = 5), cerebral palsy ( n  = 2), and degenerative central nervous system disease ( n  = 1). Surgery, which included lengthening of tendons and release of muscles, was followed by early rehabilitation at three intensity levels depending on the patients' specific needs and conditions. At 12 months follow-up there were significant improvements in all outcome measures with the following mean values: spasticity decreased by 1.4 points (Modified Ashworth Scale, 0–5), visual analogue pain score by 1.3 points, and both Canadian Occupational Performance Measures increased (performance by 3.4 and satisfaction by 3.6), and most measures of joint position or mobility improved. Hand surgery combined with early and comprehensive rehabilitation improves function, activity and patients' satisfaction in patients with disabling spasticity with improvement lasting for at least 1 year. Level of evidence: II